The Influence of Work Discipline and Compensation on the Performance of Soldiers at the Central Finance Unit I of the Army Finance Directorate (DITKUAD) - Rulik Ullafiati; Mochamad Vrans Romi (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
The purpose of this study was to determine the effect of work discipline and compensation on employee performance. This research is categorized as associative research. Hypothesis testing was conducted using multiple regression analysis. The sampling technique employed was probability sampling, using the Slovin formula. The sample consisted of 134 employees out of a total population of 200 within the Financial Work Unit I of Ditkuad. Data were processed using SPSS software version 24. The data analysis techniques included classical assumption testing, multiple linear regression analysis, hypothesis testing, and determination coefficient testing. The results showed that work discipline had a positive and significant effect on employee performance, and compensation also had a positive and significant effect on employee performance. Simultaneously, work discipline and compensation had a significant effect on employee performance.